2018
DOI: 10.1038/s41598-018-35254-1
|View full text |Cite
|
Sign up to set email alerts
|

Activation of α7 Nicotinic Acetylcholine Receptor Ameliorates Zymosan-Induced Acute Kidney Injury in BALB/c Mice

Abstract: Zymosan, a natural compound, provokes acute peritonitis and multiple organ dysfunction that affects the kidney, beside other organs via exaggerated inflammatory response. The aim of the present study is to test the role of cholinergic anti-inflammatory pathway (CAP) in alleviating acute kidney injury (AKI) induced by zymosan in BALB/c mice, using galantamine, a cholinesterase inhibitor, known to act via α7 nicotinic acetylcholine receptor (α7 nAChR) to stimulate CAP. Galantamine verified its anti-inflammatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…While such differential upregulation of p-STAT3 may reflect differential severity of renal injury, we suggest that this exaggerated upregulation of p-STAT3 in aged male HO-2 Ϫ/Ϫ mice contributed to the exacerbation of AKI observed in this setting for the following reasons. First, prior studies have shown that modalities that reduce p-STAT3 expression reduce AKI, whereas those that accentuate p-STAT3 expression exacerbate AKI (21,33,49,63). Second, in our prior study (61) in which renal HO activity was reduced because of genetic deficiency of HO-1, p-STAT3 was markedly upregulated in the ischemic kidney and implicated in the attendant exacerbation of ischemic AKI caused by HO-1 deficiency.…”
Section: Discussionmentioning
confidence: 68%
“…While such differential upregulation of p-STAT3 may reflect differential severity of renal injury, we suggest that this exaggerated upregulation of p-STAT3 in aged male HO-2 Ϫ/Ϫ mice contributed to the exacerbation of AKI observed in this setting for the following reasons. First, prior studies have shown that modalities that reduce p-STAT3 expression reduce AKI, whereas those that accentuate p-STAT3 expression exacerbate AKI (21,33,49,63). Second, in our prior study (61) in which renal HO activity was reduced because of genetic deficiency of HO-1, p-STAT3 was markedly upregulated in the ischemic kidney and implicated in the attendant exacerbation of ischemic AKI caused by HO-1 deficiency.…”
Section: Discussionmentioning
confidence: 68%
“…In addition, Hayashi et al [24,25] also found that α7nAChR not only plays a role in lung inflammation but also may downregulate the innate immune system, regulate the defensive function of cancer cells, and affect the growth and secretion function of cancer cells. Ibrahim et al [26] found that galantamine (α7nAChR agonist) can improve the survival rate of mice with acute kidney injury and improve the histopathological conditions. After α7nAChR is inhibited, this protective effect disappears, suggesting that this receptor also plays a significant role in the protection of renal inflammation.…”
Section: α7 Nicotinic Ach Receptormentioning
confidence: 99%
“… 16 , 17 In addition, activation of α7-nAChR ameliorates radiation‑induced lung injury and zymosan-induced acute kidney injury via inhibition of the high-mobility group box 1 (HMGB1)–nuclear factor‑κB (NF-κB) pathway. 18 , 19 Interestingly, EA has also been reported to ameliorate neuropathic pain via suppression of the HMGB1/NF-κB signal in the spinal cord. 20 HMGB1, an abundant inflammatory protein in the brain, is likely to involved in the pathogenesis of cognitive decline-associated diseases.…”
Section: Introductionmentioning
confidence: 99%